Developing Sustainable Agricultural Sector, as an Impetus for Macedonia`s Economic Growth - Ciglovska, Biljana (European Journal of Sustainable Development, 2018)
Agriculture is one of the most promising sectors in Macedonian economy, considering the fact that the average share of agriculture in GDP is 10% and it accounts for 17.87% of the total employment. Furthermore, if agro-processing is included the contribution to the GDP increase to 16%. Macedonia has 25.713 (km2) country area, 12.630 (km2) or 50.08% agricultural land, from which 16.4% is arable land, 1.51% permanent cropland and 39.57% forest area. With 42.7% rural population, the agriculture has important social and economic functions in Macedonian economy. Despite the third place that agriculture takes within the Macedonian economy referred to a small sector, its potential and opportunities are far greater than the current state of this sector and the results it provides. The significance of Macedonian agriculture is underestimated by official authorities. According to the World Bank Group Report for “Green Growth country assessment”, Macedonian agricultural sector is one of the sectors that need to be transformed, due to the unsustainable developing strategies used by the authorities. Therefore, the objective of this paper is to emphasize the significant advantages, strengths and the unused potential of the Macedonian agricultural sector and to provide guidelines and suggestions for turning it into growth leading sector on a sustainable basis. Sustainable development is not an abstract concept; it is the roadmap for responsible acts at a national level. For that purpose, the role of the most important stakeholders in developing process will be emphasized and discussed. Keywords: sustainable development, agriculture, reforms, economic growth